(untitled) (Vietnam Journal of Community Medicine, 2022)
The purpose: To evaluate the results of laparoscopic surgery in the treatment of endometrial cancer at Nghe An General Friendship Hospital from June 2020 to June 2022. Subjects and methods: Including 32 cases of endometrial cancer diagnosed and treated by laparoscopic surgery at Nghe An General Hospital. Study design: retrospective description. Results: 4 patients with cancer in situ, 21 patients with stage I cancer, the mean age was 56.8 years old. The average surgery time was 150 minutes. The mean number of pelvic lymph nodes removed was 1.52 right iliac nodes and 1.22 left iliac nodes. Conclusion: Laparoscopic surgery in endometrial cancer is safe and effective.